Sphingosine kinase activity and sphingosine‐1‐phosphate in the inflamed human periodontium. (20th August 2021) - Hamdan, Nader; Bhagirath, Anjali Y.; Batista, Eraldo L.
Abstract: Objectives: This study evaluated changes in the levels of Sphingosine‐1‐Phosphate (S1P) and Sphingosine Kinase (SPHK) activity in response to non‐surgical periodontal treatment in humans. Methods: Diseased ( n  = 65) and healthy sites ( n  = 72) were screened in 18 patients with localized periodontitis stage II or III. Periodontal clinical parameters were recorded, and the gingival crevicular fluid (GCF) collected at baseline, 30 and 90 days of non‐surgical treatment. Internal control sites without attachment loss/bleeding were sampled at baseline and after 90 days of treatment. SPHK activity and S1P levels and SPHK 1/2 isoforms were determined in the GCF at different time points using ELISA. Results: Non‐surgical treatment caused significant improvement in all periodontal clinical parameters ( p  < 0.01). Activity of SPHK and S1P levels was decreased ( p  < 0.05) 30 days after treatment and continued up to 90 days ( p  < 0.01); control sites remained unchanged throughout the study and resembled treated sites at 3 months ( p  > 0.05). SPHK1 levels presented decrease after periodontal treatment ( p  < 0.001). SPHK2 levels were lower than SPHK1 ( p  < 0.001) and remained unchanged. Conclusions: S1P levels and SPHK activity decreased within 3 months of non‐surgical periodontal treatment, which were correlated with improvements in periodontal parameters. Only SPHK1 levels varied significantly in the states of health and disease.